Innovation of Virtual Reality Learning Media in Increasing Vocational High School Students’ Learning Motivation in Building Management Layout Material - Hasim, Rahman; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Anam, Khaerul (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to examine the effectiveness of a learning medium that has been developed since 2024, namely VROOM: Virtual Reality Room Organization and Optimization Media, in increasing vocational high school (SMK) students’ learning motivation in the subject of Building Management Layout. The method used was Research and Development (R&D) with the ADDIE development model approach, focusing on the implementation and evaluation stages. The research subjects consisted of 30 eleventh-grade SMK students majoring in Office Management who participated in learning activities using VROOM. The data collection instrument was a student learning motivation questionnaire measuring two main aspects: intrinsic and extrinsic motivation. The results showed a significant increase in students’ learning motivation after using VROOM. Intrinsic motivation increased from 2.45 to 3.28, while extrinsic motivation increased from 2.35 to 3.22. Overall, the total score rose from 2.94 to 3.79, with a significant difference (p < 0.05) and a large effect size (Cohen’s d = 1.5). These findings indicate that VROOM effectively supports experiential and interactive learning, helping students better understand spatial concepts while increasing their motivation. Therefore, VR-based learning media has strong potential to support skill-based learning in vocational education.